Kualitas Serat Trubus Kayu Agathis Borneensis Warb - Husien, Nani; Julianto, Deny (Syntax Literate, 2025)
Agathis is one of the coniferous plants that belongs to the Araucariacea. This tree has a large trunk with few branches and is an ever green tree. Agathis stems are generally used as furniture and as raw materials for pulp, It is different from its coppicing wood that has not been widely researched. This study aims to determine the fiber quality of coppicing wood in Agathis borneensis as a producer of pulp and paper raw material fibers, through the calculation of the dimensions and fiber derivatives value. The research was conducted at the Laboratory of Biology and Wood Preservation, Faculty of Forestry, Mulawarman University. The material used is the Agathis borneensis wood trubus trunk with a height of 7 m and a diameter of 25 cm, The parts taken are from the base, middle, and end of the coppice trunk. The fiber separation process (maceration process) uses the Schultze method and a comparison table of fiber requirements as pulp and paper raw materials. The results of fiber maceration which includes length, diameter, lumens and fiber wall thickness are calculated as well as the value of fiber derivatives. The results of the study obtained an average fiber length value of 1469 μm ("short" category), an average fiber diameter of 43 μm ("large" diameter category), an average lumen diameter of 35 μm ("very large" category) and an average fiber wall thickness of 4 μm ("thin" category). The results of the calculation of the average value of the Runkel ratio are 0.24. Felting power 34.63, Flexibility ratio 0.82, Coefficient of rigidity 0.10 and Muhlsteph percentage 31.69. Based on the calculation of fiber quality values, Agathis borneensis wood trubus has fibers that are included in the fiber quality class II, category of value 310 to 450, and can be recommended as pulp and paper material.